2016
DOI: 10.1536/ihj.15-252
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Glycosylation of Lumican in Aortic Valve Stenosis Revealed by Proteomic Analysis

Abstract: SummaryTo identify proteins related to the pathophysiology of aortic valve stenosis (AS), we investigated the protein profiles of AS aortic valves. Specifically, proteins were extracted from a thickened and calcified area (AS-C) and an apparently non-thickened and non-calcified area (AS-N) in an identical aortic valve leaflet in each of 6 AS patients. The proteins were then separated by 2-dimensional gel electrophoresis (2DE). Protein spots detected by 2DE were compared between the AS-C and AS-N samples. Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The initial search yielded 196 unique records for miRNA transcriptomics, 482 for mRNA transcriptomics and 93 for proteomics in CAVD. After applying the inclusion and exclusion criteria, 5 miRNA transcriptomics [ 18 , 19 , 20 , 21 , 22 ], 5 mRNA transcriptomics [ 15 , 20 , 23 , 24 , 25 ] and 10 proteomics [ 15 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] records were eligible for the subsequent analyses ( Figure 1 A, Supplementary Figure S1, Supplementary Tables S1–S3 ). We identified only one single metabolomics study, which was only considered for integration analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The initial search yielded 196 unique records for miRNA transcriptomics, 482 for mRNA transcriptomics and 93 for proteomics in CAVD. After applying the inclusion and exclusion criteria, 5 miRNA transcriptomics [ 18 , 19 , 20 , 21 , 22 ], 5 mRNA transcriptomics [ 15 , 20 , 23 , 24 , 25 ] and 10 proteomics [ 15 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] records were eligible for the subsequent analyses ( Figure 1 A, Supplementary Figure S1, Supplementary Tables S1–S3 ). We identified only one single metabolomics study, which was only considered for integration analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In the cornea, lumican is expressed as the keratin sulfate proteoglycan, and is considered to possess the heterogeneous glycosaminoglycan [ 32 , 35 ]. Previously, various molecular weights of lumican between 37 and 250 kDa due to differences in glycosylation were detected from cell extracts by Western blot [ 36 , 37 , 38 , 39 , 40 ]. Our results also showed that various molecular weights of lumican between 37 and 250 kDa were observed in the cornea of rat, and increased lumican expression was observed in the cornea of the STZ rat (STZ) as compared to in that of the normal rat (Normal) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a later analysis, proteins related to inflammation, oxidative stress, cytoskeleton, and transport were discovered using isobaric tags for relative and absolute quantitation (iTRAQ) methodology, which allowed the identification of a specific protein profile linked to the disease and highlighted the importance of extracellular matrix proteins [74]. Procollagen C-endopeptidase enhancer 1, extracellular superoxide dismutase (Cu-Zn), immunoglobulin gamma-1 chain C region, fibrinogens, and lumican have also been shown to be altered in AS in a study using proteins extracted from thickened and calcified areas and non-diseased areas from the same valve leaflet [75]. The latter study also revealed the importance of post-translational modifications, specifically that low levels of glycosylation of lumican in the thickened and calcified areas of AS aortic valves may be associated with the pathophysiology of AS.…”
Section: Proteomics For Defining Biomarker Panelsmentioning
confidence: 99%